2023
DOI: 10.3390/diagnostics13091660
|View full text |Cite
|
Sign up to set email alerts
|

Microembolizations in the Arterial Cerebral Circulation in Patients with Atrial Fibrillation Ablation Using the Cryoballoon Technique—Protocol and Methodology of a Prospective Observational Study

Abstract: There is considerable uncertainty regarding the impact of microembolic signals (MESs) on neuropsychological abilities in patients receiving pulmonary vein isolation and beyond using the cryoballoon technique. We conducted the largest prospective observational study on this topic, providing insights into the gradual unmasking of procedure-related MESs and their impacts on neuropsychological outcomes. MESs were continuously detected periprocedurally using transcranial Doppler ultrasonography. Neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Furthermore, in a study examining the connection between epicardial fat distribution and left heart size [ 8 ], Nattel S [ 9 ] emphasized the influence of cardiac anatomy on AF, contributing to a deeper understanding of its pathogenesis. Earlier research has revealed associations between AF and climatic factors, such as air pollution [ 10 , 11 , 12 ] and temperature [ 13 ]. In a large Danish population-based study, Murphy N F et al [ 14 ] observed a significant seasonal correlation between temperature and the incidence of AF, particularly a higher occurrence during colder seasons [ 15 ], in hospitalized patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a study examining the connection between epicardial fat distribution and left heart size [ 8 ], Nattel S [ 9 ] emphasized the influence of cardiac anatomy on AF, contributing to a deeper understanding of its pathogenesis. Earlier research has revealed associations between AF and climatic factors, such as air pollution [ 10 , 11 , 12 ] and temperature [ 13 ]. In a large Danish population-based study, Murphy N F et al [ 14 ] observed a significant seasonal correlation between temperature and the incidence of AF, particularly a higher occurrence during colder seasons [ 15 ], in hospitalized patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%